Incidencia de las percepciones a las importaciones en la liquidez de Inversiones Globales Import & Export E.I.R.L. - Lima 2018 - Narváez Gonzales, Miguel Martín (2020)
This present research work has the objective to determine the impact of importation perceptions on business liquidity. The population of this research is the Peruvian company Inversiones Globales Import & Export Limited Liability Corporation, located in Lima city, taking 2018 as the year of study. The applied research design is descriptive since data was obtained from direct observation. In addition, information was collected, filtered, and consolidated from the financial statements. After analyzing, interpreting, and comparing this information, the study concluded that the importations had a negative influence on the company's liquidity, due to a decrease in its capacity to pay in the short term. Likewise, this decrease on liquidity forced the company to request external funding from banking institutions, thus generating a higher level of debt. It is recommended to prepare Projected Cash Flow and Projected Inventory Statements, as well as to improve the company collection and payment policies in order to improve its liquidity.